2016
DOI: 10.1111/ecno.12061
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Financial Development and Economic Growth: Theory and Evidence From an Instrumental Variable Approach With Human Genetic Diversity

Abstract: Because the predicted human genetic diversity created by Ashraf and Galor (2013a; American Economic Review 103: 1–46) can be considered strictly exogenous in cross‐country growth regressions, we use it and its square as instrumental variables for corruption to investigate its impact on economic growth. Our empirical finding is that corruption has both a direct, negative impact on economic growth and an indirect, negative impact through financial development. Moreover, our evidence suggests that human genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…For example, Baker et al (2006) summarize the following lines of research that provide evidence for a genetic basis of antisocial for generalized trust and 51% for trust in friends. Finally, recent cross-country empirical studies document that genetic diversity in the population is related to lower level of interpersonal trust (Arbatli et al, 2019) and corruption (Kunieda et al, 2016). To sum up, it seems that parents transmit behavioural patterns together with genes to their offspring, making genetic diversity a suitable instrument for social capital and ethical behaviour.…”
Section: Endogeneitymentioning
confidence: 99%
“…For example, Baker et al (2006) summarize the following lines of research that provide evidence for a genetic basis of antisocial for generalized trust and 51% for trust in friends. Finally, recent cross-country empirical studies document that genetic diversity in the population is related to lower level of interpersonal trust (Arbatli et al, 2019) and corruption (Kunieda et al, 2016). To sum up, it seems that parents transmit behavioural patterns together with genes to their offspring, making genetic diversity a suitable instrument for social capital and ethical behaviour.…”
Section: Endogeneitymentioning
confidence: 99%
“…An important advantage of the available database consists of a wide time period from 1984 to the present, which allows a better control on the forecast measures and adequacy of variables (Charron, 2011). Given the importance of the quality of risk measures, recent studies have applied the basis of risk analysis at the macroeconomic level (Osabutey & Okoro, 2015;Stockemer, 2013;Kunieda, Okada, & Shibata, 2016;Myles & Yousefi, 2015;Beal & Graham, 2014).…”
Section: Iii1 Data Source and Sample Delimitationmentioning
confidence: 99%
“…Consequently, these factors can help to implement policies targeting institutional reforms which are needed to promote growth-enhancing financial systems (Berhane, 2018;Blackburn & Forgues-Puccio, 2010;Casson, Giusta, & Kambhampati, 2010;Kaidi, Mensi, & Amor, 2019;Khan, Khan, Abdulahi, Liaqat, & Shah, 2019). Kunieda, Okada, & Shibata (2016). Other works, such as Keefer & Knack (1997) and Aghion, Howitt, & Mayer-Foulkes (2005), revealed that the misfunctioning of financial systems is due to corruption.…”
Section: Role Of Institutional Quality In the Finance-growth Relationshipmentioning
confidence: 99%